Pemanfaatan Augmented Reality Untuk Meningkatkan Pemahaman Kognitif Siswa Pada Materi Hewan Halal dan Haram di MTS Darul Amin - Muhammad Khair; Muhammad Iqbal; Akhmad Kastalani; Ahmad Aspiani; Jasiah, Jasiah (Edumulti: Jurnal Rumpun Ilmu Pendidikan Multidisiplin, 2025)
This study aims to see how effective the use of Augmented Reality (AR) based learning media is in helping students understand fiqh material about halal and haram animals. This study used a quantitative approach with a one group pretest-posttest design, involving 15 grade 7 students at MTs Darul Amin. Students were given tests before and after learning using AR, which displays animal models in 3D along with explanations of their laws in Islam. The results showed an increase in the average score from 60.33 to 79.47. Statistical analysis also showed that this increase was scientifically significant. The use of AR really helped students in understanding the material that was previously considered difficult. In addition to improving understanding, AR also makes the learning process more interesting and interactive. The research found that AR can be an innovative solution in learning Islamic Religious Education, especially for topics that require real visualization.